2024
DOI: 10.1021/jacsau.3c00667
|View full text |Cite
|
Sign up to set email alerts
|

Design of Highly Efficient Electronic Energy Transfer in Functionalized Quantum Dots Driven Specifically by Ethylenediamine

Wenfei Ren,
Jiguang Li,
Baiyi Zu
et al.

Abstract: The exploration of emerging functionalized quantum dots (QDs) through modulating the effective interaction between the sensing element and target analyte is of great significance for high-performance trace sensing. Here, the chromone-based ligand grafted QDs (QDs-Chromone) were initiated to realize the electronic energy transfer (EET) driven specifically by ethylenediamine (EDA) in the absence of spectral overlap. The fluorescent and colorimetric dual-mode responses (from red to blue and from colorless to yell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…From the perspective of the photophysical mechanism, 37–41 the coupling between the Flu fluorophore and the MOF framework could introduce coupled orbitals between the original HOMO/LUMO energy levels, capable of capturing the photoinduced electron–hole pairs and releasing the energy in a non-radiative transition way, thereby effectively diminishing the inherent fluorescence emission (Fig. 1b(i)).…”
Section: Resultsmentioning
confidence: 99%
“…From the perspective of the photophysical mechanism, 37–41 the coupling between the Flu fluorophore and the MOF framework could introduce coupled orbitals between the original HOMO/LUMO energy levels, capable of capturing the photoinduced electron–hole pairs and releasing the energy in a non-radiative transition way, thereby effectively diminishing the inherent fluorescence emission (Fig. 1b(i)).…”
Section: Resultsmentioning
confidence: 99%
“…[ 23 , 24 ] A series of studies proved that fluorophores, such as rhodamine‐based compounds, [ 25 ] 1,8‐naphthalimide derivatives, [ 26 ] cyanine derivatives, [ 27 ] and bodipy‐based derivatives, [ 28 ] can be used for it. In addition, nanoparticles modified with organic small‐molecule fluorescent probes, such as QDs, [ 29 ] metal‐based nanoparticles, [ 30 ] and MOFs, [ 31 ] have been introduced to construct the dual‐mode nanoprobes. [ 32 ] However, most of these probes use the colorimetric and downconversion fluorescent signals, which still suffer from the low signal‐to‐background ratio as well as interference by the colorful and fluorescent substances.…”
Section: Introductionmentioning
confidence: 99%
“…The deep understanding of intrinsic logical relations between the configurational variation and photochemical properties of the organic sensitizers has attracted considerable research interest, particularly in areas such as fluorescent dyes, fluorescent sensors, and organic luminescence devices. As one of the most fundamental and significant configurational variations caused by the excitation-strengthened hydrogen bonds, the excited-state intramolecular proton transfer (ESIPT) shows various photochemical properties involving the intramolecular charge transfer (ICT) process. The twisted intramolecular charge transfer (TICT) is a unique form of ICT that typically leads to the dissociation of the π-conjugated systems and significant changes in electron density distributions throughout the molecule. The twisting process, which involves the decoupling of the π-systems between the acceptor and the donor units, could lead to a minimal transition dipole strength between the excited and the ground states, resulting in the formation of a stable TICT state . It has been found that the strategy of utilizing the ESIPT-triggered TICT effectively maintains the torsional advantage between the countering fragments by lowering the molecular energy, which is accompanied by the destruction of the π-conjugation systems and the efficient charge transfer, ensuring a complete charge transfer and separation. Typically, the TICT process is triggered by ESIPT through both the lowering of the torsion barrier by the intramolecular hydrogen bonding and the change in the conjugated system brought by the proton transfer process itself. , Thus, the synergy of these two processes could not only make the torsional configuration more stable but also ensure an efficient electron–hole separation.…”
Section: Introductionmentioning
confidence: 99%